Rab Interacting Molecules 2 and 3 Directly Interact with the Pore-Forming CaV1.3 Ca2+ Channel Subunit and Promote Its Membrane Expression - Picher, Maria M.; Oprişoreanu, Ana-Maria; Jung, SangYong; Michel, Katrin; Schoch, Susanne; Moser, Tobias (Frontiers in Cellular Neuroscience, 2017)
Rab interacting molecules (RIMs) are multi-domain proteins that positively regulate the number of Ca2+ channels at the presynaptic active zone (AZ). Several molecular mechanisms have been demonstrated for RIM-binding to components of the presynaptic Ca2+ channel complex, the key signaling element at the AZ. Here, we report an interaction of the C2B domain of RIM2α and RIM3γ with the C-terminus of the pore-forming α–subunit of CaV1.3 channels (CaV1.3α1), which mediate stimulus-secretion coupling at the ribbon synapses of cochlear inner hair cells (IHCs). Co-expressing full-length RIM2α with a Ca2+ channel complex closely resembling that of IHCs (CaV1.3α1-CaVß2a) in HEK293 cells doubled the Ca2+-current and shifted the voltage-dependence of Ca2+ channel activation by approximately +3 mV. Co-expression of the short RIM isoform RIM3γ increased the CaV1.3α1-CaVß2a-mediated Ca2+-influx in HEK293 cells, but disruption of RIM3γ in mice left Ca2+-influx in IHCs and hearing intact. In conclusion, we propose that RIM2α and RIM3γ directly interact with the C-terminus of the pore-forming subunit of CaV1.3 Ca2+ channels and positively regulate their plasma membrane expression in HEK293 cells.